Tranz Liberation Framework - Henry, Charles (New Zealand Sociology, 2025)
The Tranz Liberation Framework was developed in response to the discourse in Aotearoa/New Zealand during the Posie Parker visit in March 2023. Although there was overwhelming support for trans folks, it did not translate into improved conditions for the community. The framework takes Nancy Fraser’s theory of justice and explains the specific aspects of life that need to change in order for transgender and non-binary people to be equal members of society. It includes three pillars that are required for acceptance of transgender and non-binary people within wider society: protection, access and recognition. The framework can be applied by a range of different groups to fight for a world where transgender and non-binary people have the same opportunities to participate in society as cis people experience, while being able to live as their authentic selves. Please note this article contains the author’s personal views in their personal capacity.